Implications of MAVEN Mars near‐wake measurements and models. Issue 21 (11th November 2015) - Luhmann, J. G.; Dong, Chuanfei; Ma, Yingjuan; Curry, S. M.; Mitchell, D.; Espley, J.; Connerney, J.; Halekas, J.; Brain, D. A.; Jakosky, B. M.; Mazelle, C.
Abstract: Mars is typically viewed as a member of the category of weakly magnetized planets, with a largely induced magnetosphere and magnetotail produced by the draped fields of the solar wind interaction. However, selected Mars Atmosphere and Volatile EvolutioN Mission (MAVEN) suprathermal electron and magnetic field observations in the near wake, sampled along its elliptical orbit during the early prime mission at altitudes ranging from its ~150 km periapsis to the tail magnetosheath, reinforce a picture seen in an MHD model where magnetic fields are rooted in the planet throughout much of the Martian magnetotail. Key Points: Mars' solar wind interaction is often viewed as an induced magnetosphere type MHD models of the interaction suggest much of its wake magnetic flux is instead rooted in Mars MAVEN measurements show some support for this alternate picture, at least at the present epoch